Growth and physical development of primary schoolchildren in Etimesğut, Turkey - Nashed, Salwa; Bertan, Münevver (The Turkish Journal of Pediatrics, 1968)
The growth and physical development of primary schoolchildren in Etimesgut, Turkey, were investigated through physical examination and measurement of height and weight. The mean height and weight of the Etimesgut children are compared with the Turkish Standard, American, Egyptian and Haitian schoolchildren. The Etimesgut boys and girls were found to be taller than the Turkish Standard and the Haitian children, except for Haitian girls aged 12 to 14. The Etimesgut children were similar in height to Egyptian children until the age of 12 for boys and 13 for girls and shorter than American children. Etimesgut children were found to be heavier than Haitian children and lighter than American children. When the weight was calculated in relation to the age, Etimesgut children were heavier than Haitian children at every age and American and Egyptian children at some ages, indicating that the factors which affect body growth influence both height and weight development. The incidence of angular stomatitis among Etimesgut primary schoolchildren corresponded with the deficiency of riboflavin reported in 39 per cent of the families in this area. The incidence of enlarged tonsils was high in both sexes. Dental caries were found to be lower than in British schoolchildren, possibly owing to the amount of fluoride in Etimesgut's water. Impaired vision was higher in the 7 to 10 year age group than in the 11 to 14 year group, higher in girls than in boys, but lower than that of Swedish nomad Lapp children. Hip dislocation was diagnosed in three girls and congenital heart disease in one girl.